Letter - Winstanley, E.
030-0026-001 Telegraphic Address, Inland - "Wholesale, Manchester." Foreign - "Copexport, Manchester." Telephone: Blackfriars 1212. Extension No. 87 Please address your reply: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. Cable codes: A.B.C. 6th and 7th editions; Western Union 8 Letter; Bentley Complete Phrase; Bentley Second Phrase; A.I. Marconi, and private. OUR REFERENCE EXPORT ST/HP. 1733 YOUR REFERENCE 15th October, 1938. The Trades Union Congress General Council, Transport House, Smith Square, LONDON. Dear Sirs, We beg to refer to our telephonic conversation of this morning, and to the order you have placed with us for Dried Cod, Soap and Sandals for shipment to Spain, for which we thank you. We have placed the orders into work for immediate shipment, but doubt whether it will be possible to send forward by next Wednesday's steamer from Garston to Rouen, but confidently anticipate being able to arrange shipment by the following steamer on the 26th instant. In this regard, however, we will write you further when definite information is in our possession. Meanwhile, we are pursuing enquiries regarding Needles and Knitting Wools which you have asked us to secure on your behalf and will write you regarding same as early as possible. Yours faithfully, E. Winstanley Export Department. 292/946/30/26